2019
DOI: 10.1177/0165551519865489
|View full text |Cite
|
Sign up to set email alerts
|

Does open access citation advantage depend on paper topics?

Abstract: Research topics vary in their citation potential. In a metric-wise scientific milieu, it would be probable that authors tend to select citation-attractive topics especially when choosing open access (OA) outlets that are more likely to attract citations. Applying a matched-pairs study design, this research aims to examine the role of research topics in the citation advantage of OA papers. Using a comparative citation analysis method, it investigates a sample of papers published in 47 Elsevier article processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 73 publications
(107 reference statements)
1
11
0
Order By: Relevance
“…Apart from that, the citation advantage is usually used as recognition of the validity of OA publication and has been linked to the authors' selection of their best works for OA. However, the study by Sotudeh (2019) concludes that, if the authors' self-selectivity exists, it is not responsible for the OA citation advantage, at least with regard to the selection of topics. Besides, during her data collection, Antelman (2004) observed that it was usual for authors to publish all or none of their articles in OA.…”
Section: Introductionmentioning
confidence: 98%
“…Apart from that, the citation advantage is usually used as recognition of the validity of OA publication and has been linked to the authors' selection of their best works for OA. However, the study by Sotudeh (2019) concludes that, if the authors' self-selectivity exists, it is not responsible for the OA citation advantage, at least with regard to the selection of topics. Besides, during her data collection, Antelman (2004) observed that it was usual for authors to publish all or none of their articles in OA.…”
Section: Introductionmentioning
confidence: 98%
“…A study of working papers in economics shows that the impact of working papers is relatively low and provides no evidence of an OA advantage (Frandsen, 2009). OA advantages might be topic-dependent; that is, authors tend to select citationattractive topics, especially for OA outlets that are more likely to attract citations (Sotudeh, 2019). However, we do not really know whether OA benefits hot topics or TA cools cold topics.…”
Section: Journal Of Data and Information Sciencementioning
confidence: 92%
“…Unrestricted access to scientific work manifests the principle that science is owned collectively by the public (i.e., the norm of communalism; Merton, 1942Merton, /1973. OA also improves a work's reach and impact metrics; papers that are publicly accessible get more engagement and more citations relative to inaccessible research (Davis, 2011;Fraser et al, 2020;Fu & Hughey, 2019;Piwowar et al, 2018;Sotudeh, 2020;Tennant et al, 2016). Nominal support for OA has been high for more than a decade among psychologists (Dallmeier-Tiessen et al, 2011) and health researchers (Anderson et al, 2007(Anderson et al, , 2010).…”
Section: What Are Preprints?mentioning
confidence: 99%